Tarsonemid mites (Acari: Tarsonemidae) on myrtaceous plants of the Atlantic Forest, Brazil, with description of a new species of Tarsonemus Canestrini & Fanzago - Demite, Peterson R.; Cavalcante, Ana C. C.; Lofego, Antonio C.; Rodrigues, Ricardo R.; Moraes, Gilberto J. De (Zootaxa, 2022)
A survey of tarsonemid mites associated with plants of the family Myrtaceae was conducted in seven areas of the Atlantic Forest biome. Fourteen known species were registered; other 21 morphospecies was identified up to genus level. Additionally, a new species, Tarsonemus conduru Lofego & Cavalcante sp. nov. is described based on specimens collected in the Atlantic Forest of Bahia state.